ANALISIS INTERAKSI TANAH-GEOFOAM TERHADAP PARAMETER KUAT GESER TANAH - Sitompul, Emmanuel Pangihutan; Desiani, Asriwiyanti (JMTS: Jurnal Mitra Teknik Sipil, 2025)
The ground in the Gedebage area of Bandung city consists of soft soil at a depth of approximately 30 meters. Construction on soft soil generally suffers from high settlement and low bearing capacity. To overcome the problem of soft soil, a lightweight material solution is needed that still has the necessary strength. This research uses geofoam, a synthetic material made of EPS (expanded polystyrene), as a geotechnical material. The interaction between soil and geofoam has not been widely studied, while the use of interface value software applications are always required for the geotechnical analysis process. This study aims to analyze the effect of geofoam layer on soil shear strength parameters in Gedebage area, Bandung and geofoam interaction. The soil samples used were undisturbed soil at a depth of 2.0-2.5 meters. The test conducted was the consolidated drained (CD) type direct shear test using geofoam of PT X with the type of Geofoam EPS with geofoam sample dimensions for testing 6 cm in diameter and 1 cm in height. The results showed that the Geofoam affected the shear strength parameters of the native soil. In the direct shear test of the native soil, the cohesion value (c) was found to be 0.0392 kgf/cm2 and the internal shear angle was 23.44 degree. While in the direct shear test of native soil with Geofoam, the cohesion value (c) was 0.5598 kgf/cm² and the internal shear angle was 7.02 degree. The Rinterface value of the interaction between soil and Geofoam is 0.284